The multidisciplinary management of cholangiocarcinoma. Issue 2 (16th November 2022) - Ohaegbulam, Kim C.; Koethe, Yilun; Fung, Alice; Mayo, Skye C.; Grossberg, Aaron J.; Chen, Emerson Y.; Sharzehi, Kaveh; Kardosh, Adel; Farsad, Khashayar; Rocha, Flavio G.; Thomas, Charles R.; Nabavizadeh, Nima
Abstract: Cholangiocarcinoma is a lethal malignancy of the biliary epithelium that can arise anywhere along the biliary tract. Surgical resection confers the greatest likelihood of long‐term survivability. However, its insidious onset, difficult diagnostics, and resultant advanced presentation render the majority of patients unresectable, highlighting the importance of early detection with novel biomarkers. Developing liver‐directed therapies and emerging targeted therapeutics may offer improved survivability for patients with unresectable or advanced disease. In this article, the authors review the current multidisciplinary standards of care in resectable and unresectable cholangiocarcinoma, with an emphasis on novel biomarkers for early detection and nonsurgical locoregional therapy options. Abstract : In this study, the authors review the current multidisciplinary standards of care in resectable and unresectable cholangiocarcinoma, with an emphasis on novel biomarkers for early detection and nonsurgical locoregional therapy options.